(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
ABSTRACT Objective: To find the outcome of Kelafong procedure in the treatment of spinal tuberculosis Methods: This prospective study was conducted on 8 patients diagnosed with active spine tuberculosis in the Department of Orthopedics Khyber Teaching Hospital, Peshawar from august, 2015 to December 2017 who underwent Kalafong procedure. Efficacy of Kalafong procedure was noted as improvement in neurological symptoms of a patient with spinal tuberculosis i.e. paraplegia, bowel and bladder symptoms after the Kalafong procedure measured according to Frankel et al [6] at the time of 06 months follow-up. Data was analyzed with SPSS version 20. Results: The mean age of the patient was 50.35 years ±2.53SD with the age range of 15 to 55 years. There were 6 (75%) females and 2 (25%) males. The mean pre operative cob angle was 45.15 ± 2.73SD. The post operative Cobb angle was 42.38 ± 2.68SD. Three (37.5%) patients improved to nurological status A and B while 2 (25%) patients improved to Cnurological status. Conlcusion: Kelafong procedure is effective in the treatment of spinal tuberculosis regarding improvement in neurological status.